Persona Pronoun on the Song Lyrics of KLA Project and Its Relevance to Students Linguistic Knowledge BIPA A1 - Sudaryanto Sudaryanto; Nurul Raihan Lathifah; Sholeha Rosalia (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2019)
One element of the competence of Indonesian language learners for foreign speakers (BIPA) A1 is mastering the knowledge of the use of pronouns. In the field of linguistics, person pronouns can be called person pronouns. This descriptive study describes the person pronouns in the KLA Project song lyrics, like song “Yogyakarta”, “Gerimis”, “Tak Bisa ke Lain Hati”, “Bunda”, and “Dunia Baru”. The KLA Project songs can be used as a medium for mastering the linguistic knowledge of foreign speakers (BIPA) A1, especially the person pronouns. Based on the results of the analysis of KLA Project song lyrics, there is a single person pronoun singular (-ku, ku-, aku), second person pronoun singular (-mu, dikau, engkau, kau-), third person pronoun singular (-nya), third person pronoun plural (mereka), and inclusive person pronoun (kita). KLA Project song lyrics that contain the person pronoun are used as  teaching material for BIPA A1 speakers through crosword puzzles (Teka-Teki Silang, TTS) and see and complete the lyrics.